Electrical charactrization of III-V antimonide/GaAs heterostuctures grown by Interfacial Misfit molecular beam epitaxy technique - Aziz, Mohsin (2014)
Lattice mismatched heterostructures grown by Interfacial Misfit (IMF) technique, which allows the strain energy to be relieved both laterally and perpendicularly from the interfaces, are investigated. However, electrically active defects are created at the interface and away from the interface with energy levels deep in the bandgap of the host materials. These defects dramatically affect the optical and electrical properties of the devices. In this thesis, an investigation of deep level defects is carried out on GaSb/GaAs uncompensated and Te compensated heterostructures grown by the IMF method using DLTS, Laplace DLTS, I-V, C-V, C-F and C-G-F measurements. Furthermore, the effect of thermal annealing treatments on the defect states is also studied on both types of samples. It was found that the well-known EL2 electron trap is commonly observed near to the interface of both uncompensated and Te compensated GaSb/GaAs IMF samples. However, several additional electron defects are detected in Te compensated samples. Rapid thermal annealing performed on uncompensated samples resulted in the annihilation of the main electron trap EL2 at a temperature of 600 oC. On the other hand rapid thermal annealing and conventional furnace annealing were carried out on Te compensated samples, and it was observed that rapid thermal annealing process is more effective in terms of defects reduction. The density of interface states is determined from C-G-F and forward bias DLTS measurements. Te compensated samples exhibit the highest density of interface states and have additional hole traps as compared to uncompensated samples. The electrical properties of p-i-n GaInAsSb photodiodes grown on uncompensated and Te compensated GaSb/GaAs templates on GaAs substrates using special growth mode are investigated. The non-radiative defects which could have detrimental effects on the performance of these photo diodes are studied here for the first time. Both electron and hole defects are detected, and their capture cross-section measurements reveal that some of defects originate from threading dislocations. The double pulse DLTS measurements are performed and the concentration distributions of the detected defects are determined.